(untitled) (Lanham, 1990)
Contains a provocative, challenging analysis of the potential development of economic and strategic relations between the U.S., Japan, and China. The book focuses on an analysis of the potential economic relations between these three countries and how these relations will affect other countries, both economically and strategically. The relationship between the world's two greatest economic powers, the U.S. and Japan, and the world's most populated country, the PRC, will greatly influence the future of the political, economic, and security posture of the Pacific Basin area. Co-published with the Center for International Security and Strategic Studies.
Keywords: Dự báo kinh tế,Economic forecasting; Thái Bình Dương,Pacific Area